Multilingual trends in a globalized world : prospects and challenges - Singh, Navin Kumar (Cambridge Scholars Publishing, 2013)
This book presents evolving language education trends by drawing examples and case studies from around the world. Over the past few decades, significant economic and political changes have taken place around the world which have had a significant impact on language teaching and learning practices across the globe. With globalization, the focus of language education has shifted from monolingualism towards bilingualism and multilingualism, in that multilingual practices have become the norm rat ...